HAMILTONIAN FORMULATION OF DUST CLOUD COLLAPSE - Kwidzinski, Nick; Malafarina, Daniele; Ostrowski, Jan J.; Piechocki, Włodzimierz; Schmitz, Tim (arxiv, 2020)
We consider the gravitational collapse of a self-gravitating spherical dust cloud in the Hamiltonian formalism. We address both homogeneous and inhomogeneous cases. Our novel derivation of the Hamiltonian of the system is based on an improved variational prin ciple. It differs from usual treatments due to the presence of an extra boundary term added to the Hilbert action. As expected, the standard equations of motion are retrieved. How ever, differently from other treatments, the total Hamiltonian obtained with our procedure in the Schwarzschild time-gauge is identical to the total mass of the system as measured from infinity, as it would be expected. Implications for the quantization of the system are suggested
Keywords: Type of access: Open Access; dust cloud collapse; Hamiltonian formulation